2020
DOI: 10.4995/wpom.v11i1.12891
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model for aircraft routing and crew scheduling: Lagrangian Relaxation and metaheuristic algorithm

Abstract: <p>Airline optimization is a significant problem in recent researches and airline industrial as it can determine the level of service, profit and competition status of the airline. Aircraft and crew are expensive resources that need efficient utilization. This paper focuses simultaneously on two major issues including aircraft maintenance routing and crew scheduling. Several key issues such as aircraft replacement, fairly night flights assignment and long-life aircrafts are considered in this mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the previous models, the effective use of the fleet in airlines facing investment restrictions has not been considered. This paper is based on a recently done research by Mirjafari et al (2020). They formulated an integrated model of aircraft routing and crew scheduling to minimize airline costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous models, the effective use of the fleet in airlines facing investment restrictions has not been considered. This paper is based on a recently done research by Mirjafari et al (2020). They formulated an integrated model of aircraft routing and crew scheduling to minimize airline costs.…”
Section: Discussionmentioning
confidence: 99%
“…Several researches in the literature were focused on integerating AMRP with other aviation problems (Gürkan et al , 2016; Ben Ahmed et al , 2017a, 2017b; Kammoun and Rezg, 2018; Ben Ahmed et al , 2018; Kenan et al , 2018a; Kenan et al , 2018b; Parmentier and Meunier, 2020; Wei et al , 2020; Chen et al , 2020; Qin et al , 2020). In this regard, Mirjafari et al (2020) consider several impactful issues that include aircraft replacement, fairly night flight assignment, deadhead flights and long-life aircraft, integerated aircraft maintenance routing and crew scheduling. Based on flight hour cutoff point, a new framework was introduced to handle maintenance checks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Heuristic techniques has been used to solve various integer programing problems. Mirjafari et al (2020) used Lagrangian relaxation to solve their integrated model for aircraft routing and crew scheduling. The outcome shows the results were better than metaheuristic techniques.…”
Section: Benders’ Decompositionmentioning
confidence: 99%
“…The findings demonstrated that the suggested model could improve CRP solutions compared to previous studies. Mirjafari et al [ 29 ] presented an integrated model for aircraft routing and CSP with the aim of minimizing crew, aircraft replacement, maintenance, and deadhead flight costs. They suggest a new frame for maintenance operations based on flight hours.…”
Section: Literature Reviewmentioning
confidence: 99%